Some like it organic, some like it purple and some like it ancient: Consumer preferences and WTP for value-added attributes in whole grain bread. (September 2016) - Teuber, Ramona; Dolgopolova, Irina; Nordström, Jonas
Highlights: Consumer liking and willingness to pay for value-added attributes in bread is studied. A combination of hedonic evaluation plus experimental auctions is employed. Extrinsic information leads to a better taste experience. However, the impact is not uniform but differs significantly across bread types. Hedonic scores and reference prices are the major determinants of WTP. Abstract: The German bread market is considered one of the most developed and diverse bread markets worldwide. However, until so far no empirical evidence exists with respect to consumers liking and willingness to pay for different value-added attributes in whole grain bread. Thus, our study is the first one providing empirical evidence on how German consumers perceive different value-added attributes in whole grain bread, how much they are willing to pay for these attributes and to which extent liking scores and willingness to pay (WTP) estimates are influenced by extrinsic information. Our analysis is based on a combination of hedonic evaluations with experimental auctions under three different information scenarios. The attributes considered in our study are: (i) organic, (ii) functional, and (iii) ancient grain variety. The collected data are analyzed via cluster analysis and random effects Tobit models. The results indicate the following. First, significant heterogeneity exists across consumer clusters with respect to the responsiveness to extrinsic information. Second, results differ depending on the hedonic measure chosen, i.e. whether a taste or an overall liking score is employed. Third, the chosen functional bread, purple wheat bread would be accepted as long as taste expectations are met. Put differently, consumers would not comprise on taste for health. However, at the same time our results highlight that expecting that a bread has "natural" health-enhancing properties significantly increases the sensory evaluation and thus product liking. Consequently, bread with functional properties will be only successful on the market if consumers are satisfied with the taste experience, whereas extrinsic information might increase the perceived taste experience.